HAKIM DAN MEDIASI:: Pemaknaan Hakim Terhadap Mediasi Perkara Perdata di Pengadilan Negeri Pekalongan - Shinta Dewi Rismawati; Saif Askari; M. Muslih Husein (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2012)
This sociolegal research was aimed to understrand the judgeís comprehension toward mediation in private lawsuit procession. This comprehension was so urgent in order to understand how pragmatism practice could infiltrate in law court. To do so, I used symbolic interaction approach and model to analyze the data, that snowball-purposively gathered from the Judges. The locus of this study located in Pekalongan District Court (Pengadilan Negeri). The study showed some divergences opinion among judges in understanding the laws/norms/statutes of mediation both, textually and contextually (as they applied the text of norm in their cases). So, it effected on the implimentation of enforcement and made them tend to pragmatic in doing mediation as formalistic-routine procedure. The roots of this attitude came from internally factors such pragmatism itself and externally ones, pragmatism among the parties of lawsuit and their advocaats.